INFORMATION SYSTEM FOR BORROWING AND RETURNING BOOKS AT MANDA ELU PRIVATE HIGH SCHOOL - Rosalia Padaka; Adelbertus Umbu Janga; Mitra Permata Ayu (CV. Fahr Publishing, 2023)
In the current era of globalization, the world of information is developing very rapidly because it is supported by increasingly sophisticated technological developments. Computers are a tool to support the development of information technology. Therefore, an institution that uses computers to manage its information system will have more value than a system that is processed manually. Current technological developments are very diverse in various aspects of life so that they really help human activities every day. This includes the development of computer technology with various applications used in various scientific disciplines. It is hoped that this technology, which was born thanks to human creativity and innovation, can regenerate creativity and new innovations in various fields that mark the progress of this technology. One area that cannot be separated from the use of technology is education. Hardware and software. Hardware includes one notebook unit with eighth generation Intel Core i3 specifications, 4 Gb RAM, 256 Gb SSD. The software used includes the Windows 10 Pro 64bit operating system, Notepad++, XAMPP, Chrome, Microsoft Word, Microsoft Visio.The results obtained from this research are an information system for borrowing and returning books that can solve the problems faced by Manda Elu Private High School. From the results of the discussion it can be concluded that the information system for borrowing books and returning books can answer the problems faced, including making data searches easier and faster, archiving data does not take up a lot of space because it has been replaced by digital storage, and data reporting can be presented quickly and completely. , attractive and suitable for office needs. Keywords: information system, book lending, website